唾液酸化還元電位の日内変動と月内変動に関する検討 : 鍼灸臨床における客観的評価法の確立を目指して - 金野, 彰子; 渡邉, 勝之; 佐藤, 貴恵; 嶋田, 晃 (人体科学, 2010)
The aim of this study is to reveal the usage of Saliva ORP (Oxidation Reduction Potential) as a method for objective assessment in acupuncture practice. We investigated the relationship between the diurnal and monthly variation of Saliva ORP and subjective assessment. In diurnal variation, the Saliva ORP levels were maintained at the subjects' resting state. In contrast, Saliva ORP had a tendency to increase on-duty and was recovered by sleeping. The subjects that were sleep deprived revealed the same high levels of Saliva ORP as the night before. In a monthly variation, students' Saliva ORP levels that were having many exams had a tendency to increase along the time while in student subjects with fewer exams the levels only increased at the exam time. There was no significant correlation between Saliva ORP and subjective assessment. However, these results suggest Saliva ORP measurement as a good method to objectively evaluate the state of physical and mental health.